Sacred Speech and Written Word: Hebrew–Yiddish Diglossia in Hasidic Homiletics - Daniel Reiser (Religions)
This article examines the complex linguistic phenomenon of Hebrew–Yiddish diglossia within Hasidic homiletic literature, particularly focussing on sermons from the nineteenth and twentieth centuries. While previous scholarship has emphasised Hebrew’s dominance in Hasidic written works, this study demonstrates how Yiddish has played a crucial role in preserving and transmitting Hasidic teachings. Through analysis of primary sources, three distinct models of Hebrew–Yiddish integration are identified: parallel texts in both languages within the same volume, limited Yiddish passages integrated within predominantly Hebrew texts, and a complete amalgamation where the languages become nearly inseparable. Analysis indicates that Hasidic authors and editors deliberately preserved Yiddish elements to maintain the authenticity of the tzaddik’s original oral teachings while adhering to Hebrew’s traditional status in religious literature. This linguistic practice elevated Eastern Yiddish’s cultural position concurrent with similar (but different) developments in Haskalah literature. Furthermore, the study demonstrates how Hasidic literature’s incorporation of spoken Yiddish into sacred texts contributed to the language’s legitimisation as a medium for religious discourse. This examination offers new perspectives on linguistic hierarchies in religious Jewish texts and illuminates how Hasidic literature developed innovative solutions to balance authenticity and tradition in religious writing.